Konsep Keadilan dalam Ekonomi Syariah - Dewi, Kemala; Jamal, H. Khairunnas (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The concept of justice in Islamic economics as a fundamental principle underlying all economic and social interactions. This study explains the dimensions of distributive and commutative justice, as well as the application of the principle of justice through Islamic economic instruments such as zakat, infaq, and profit-sharing systems. Emphasis is placed on the role of Islamic financial institutions that implement a system without usury and transparent transactions based on profit sharing. However, the implementation of justice faces challenges in the form of the dominance of capitalism, limited public understanding, and less than optimal regulations. This study concludes that the application of justice in Islamic economics can create equitable social welfare and become the foundation for sustainable economic development.